The Ethical Dilemma in the Bhagavadgita - Lehtonen, Tommi (Society for Indian Philosophy and Religion, 2024)
This article sheds new light on the much-discussed ethical dilemma in the Bhagavadgītā concerning whether human duty or the consequences of action should be the focus of ethical concern. According to a common view, the text advances duty-based ethics through the mouth of Krishna, whereas Arjuna appeals to consequentialist considerations. In contrast, another view argues that Krishna’s ethical thinking is a distinctive kind of rule-consequentialism that conceives of the twin consequences of liberation (mokṣa) and the common good (lokasaṅgraha) as intrinsically valuable. This article argues that the concept of desireless action (niṣkāmakarma) is crucial to answering the ethical dilemma in the Bhagavadgītā. Several pieces of evidence suggest that the text does not associate desireless action with a desire to act for the common good but instead conveys an attitude called, for lack of a better expression, ‘inaction in action and action in inaction’ (4.18) toward the results and consequences of action in general. When individuals act with this attitude, they focus on the action itself (i.e., changes corresponding to the action), not its ultimate effect (i.e., results and consequences). Thus, in acting, individuals should have an attitude akin to the attitude taken in inaction, in that they do not expect the outcome of the action to be as envisioned or to be to their advantage—nor do they not consider themselves morally entitled to the outcome of the action. Such an attitude of non-ownership transcends the distinction between duty-based ethics and consequentialist ethics, for the doers of actions consider themselves as an intermediate link in the long chain of causes and effects, regardless of their personal merit, not as individuals who deserve praise for their dutiful work and accomplishments.
Keywords: fi=Viestintätieteet|en=Communication Studies|